Química mineral e geotermometria dos condritos comuns Campos Sales e Santa Vitória do Palmar. - Gazillo Neto, Ricardo (2018)
The Campos Sales and Santa Vitória do Palmar are two ordinary chondrites of the same chemical group but with different stages of thermal metamorphism. The Campos Sales (CS) chondrite has a high grade of recrystallization being classified as L5 group and Santa Vitória do Palmar (SVP) is a primitive ordinary chondrite that has low metamorphic grade, preserving the original textures with a fine grained amorphous and cryptocrystalline matrix and with a relative pristine mineralogy composed primarily of clinobronzite, pigeonite and olivine where it is classified as L3 group. Electron microprobe analyses from CS chondrite show little deviation of an average molar composition value for the olivine and orthopyroxene, also revealing the presence of plagioclase with oligoclase-anorthoclase composition and diopside inside some microcrystalline chondrules. Phosphates and chromite wereas also identified in the CS, where the phosphates are apatite and merrillite. Both chondrites belong to the L chemical group which indicates the same parent body. The SVP chondrite has two distinct types of plagioclase, one is anorthitic in composition, which maybe indicates a primary cosmochemical formed mineral and the other is oligoclase with high impurities of magnesium, indicating a low degree of mesostasis recrystallization; SVP chondrule olivines together with the anorthitic plagioclase were analyzed to look for their relict patterns of nebular condensates. Geothermometry of the CS were made using the equilibrated system enstatite-diopside geothermometer through the analysis of recrystallized microcrystalline chondrules revealing the peak metamorphic temperature for this equilibrated chondrite.